2012
DOI: 10.1099/vir.0.045088-0
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a model of lethal dengue virus 2 infection in C57BL/6 mice deficient in the alpha/beta interferon receptor

Abstract: Dengue virus (DENV) causes dengue fever and dengue haemorrhagic fever/dengue shock syndrome, both considered major public-health problems worldwide. We generated a lethal DENV-2 strain (D220) by 10 additional cycles of subcutaneous inoculation of mice with supernatant from mosquito cells infected with the previously characterized strain D2S10, followed by harvesting of serum. D220 induces mortality at ten-fold lower doses than D2S10 in mice lacking only the alpha/beta interferon (IFN-a/b) receptor in C57BL/6 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
133
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 117 publications
(139 citation statements)
references
References 22 publications
5
133
0
Order By: Relevance
“…This method caused neurotropic disease and paralysis, neither of which is typically observed in humans. More recently, immunocompromised mice lacking type I and/or type II IFN receptors have been generated (10,11). Dengue infection in these mice recapitulates some aspects of the human disease, such as cytokine storm, vascular leakage, TNF-␣ production, hemorrhage, and nonparalytic death (36).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This method caused neurotropic disease and paralysis, neither of which is typically observed in humans. More recently, immunocompromised mice lacking type I and/or type II IFN receptors have been generated (10,11). Dengue infection in these mice recapitulates some aspects of the human disease, such as cytokine storm, vascular leakage, TNF-␣ production, hemorrhage, and nonparalytic death (36).…”
Section: Discussionmentioning
confidence: 99%
“…However, the complete absence of IFN signaling renders these mice profoundly immunodeficient (reviewed in reference 5), which means data generated in these animals must be interpreted with caution. A recent report proposed an improvement to the AG129 model; mice lacking the IFN-␣/␤ receptor but with intact IFN-␥ signaling were highly susceptible to lethal infection with a mouse-adapted dengue virus strain and thus were proposed by the authors to be more useful for vaccine testing than the AG129 mice (10). However, the potential impact of a global lack of type I IFN receptor (IFNAR) signaling on the immune response to both dengue virus infection and vaccination cannot be overlooked.…”
mentioning
confidence: 99%
“…Recently, DENV-2 strains have been identified that produce a disease that contains features of the human illness, such as thrombocytopenia, viraemia, cytokine storm, and/or vascular leakage (Shresta et al, 2006;Tan et al, 2010;Mota & RicoHesse, 2009). Lethal DENV-2 infection models have been described in immunocompromised mouse strains, particularly in AG129 mice, deficient in IFN-a/b receptor (IFN-a/ bR) and IFN-c receptor (IFN-cR) signalling, and A129 and ifnar 2/2 mice, deficient in IFN-a/bR only (Johnson & Roehrig, 1999;Orozco et al, 2012;Prestwood et al, 2012;Zellweger et al, 2010;Balsitis et al, 2010). Other strains of immunocompromised mice are resistant to lethal infection by DENV-2, such as mice deficient in IFN regulatory factors 3 and 7 (IRF3 and IRF7), signal transducer and activator of transcription factor 1 or 2 (STAT1 or STAT2), and mitochondrial antiviral signalling protein (MAVS) (Chen et al, 2013;Perry et al, 2009Perry et al, , 2011Ashour et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…IFN-cR signalling is sufficient for mouse resistance to TVP-376, but resistance to D2S10 requires both IFN-a/bR and IFN-cR Studies with DENV-2 strains have shown that AG129 mice are more susceptible to infection than A129 mice (Orozco et al, 2012;Prestwood et al, 2012). However, no studies have been conducted with the other DENV serotypes.…”
mentioning
confidence: 99%
“…This is particularly informative because DENV does not cause relevant disease in immunocompetent mice unless extremely high inoculums are used (43)(44)(45)(46)(47)(48)(49)(50)(51). Using these valuable antibodies in ADE studies with primary human monocytes allows identification of important signaling pathways that represent potential therapeutic targets for the treatment of severe dengue disease.…”
Section: Dengue Virus (Denv)mentioning
confidence: 99%